Исследование спектрально-люминесцентных свойств металлокомплексов дипиррометенов - Ашмарина, Мария Владимировна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
The spectral-luminescent properties of metal complexes of zinc and cadmium dipyrromethenes with various halogen ligands in the series of alcohol solvents have been experimentally studied. It was found that the replacement of the metal in complexing agent leads to a long-wavelength shift in the absorption and luminescence spectra. Additionally, the introduction in the ligand of bromine and iodine atom increases the lifetime of the triplet state due to an increase in the yield of intercombination conversion by the “heavy atom” mechanism compared to complexes without halogens in the ligand. Due to this, the long-lived radiation of the metal complexes of dipyrromethenes was found and its was studied in frozen solutions. Preliminary results of the study indicate the possible use of such complexes as sensors and photosensitizers for the generation of singlet oxygen.